Pengaruh Fitur Live Streaming Terhadap Pembelian Impulsif Gen Z Melalui Platform E-Commerce - Nimas, Annurudzati; Nurhadi (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2026)
This study aims to analyze the influence of live streaming features on impulsive buying behavior among Generation Z through trust in the Shopee e-commerce platform. In today’s fast-paced digital era, live streaming has become an innovative marketing strategy offering real-time, interactive, and engaging shopping experiences. Generation Z, known for their tech-savviness, is the primary target of this trend. This research employs a quantitative approach using purposive sampling on 200 respondents, all Generation Z Shopee users residing in Surabaya. The independent variables include product demonstration, flash sale, and influencer collaboration; the mediating variable is consumer trust; and the dependent variable is impulsive buying. Data was collected through questionnaires and analyzed using the Partial Least Square (PLS) method. The results show that product demonstrations, flash sales, and influencer collaborations significantly affect consumer trust and impulsive buying decisions. Furthermore, consumer trust acts as a significant mediator between live streaming features and impulsive buying behavior. This research provides practical implications for e-commerce platforms to enhance digital marketing strategies by optimizing live streaming features to improve customer experience and stimulate impulsive purchases among Generation Z.Keywords: Live Streaming, Consumer Trust, Impulsive Buying, Generation Z, Shopee.